Efektivitas Seed Coating pada Benih Cabai Rawit (Capsicum frutescens L.) Varietas Bara yang Kadaluarsa - Aulia Azzahrah Akhyak Putri; Ida Retno Moeljani; Nova Triani (BPFP Universitas Bengkulu, 2025)
[EFFECTIVENESS OF SEED COATING ON EXPIRED ‘BARA’ BIRD’S EYE CHILI (Capsicum frutescens L.) SEEDS]. The decline in physiological quality of bird’s eye chili (Capsicum frutescens L.) seeds due to prolonged storage poses a significant challenge in horticultural crop production, particularly in ensuring the availability of high-quality seeds. This study aimed to evaluate the effectiveness of seed coating using carboxymethyl cellulose (CMC) and humic acid in combination with Plant Growth Promoting Rhizobacteria (PGPR) in enhancing the viability and vigor of aged ‘Bara’ chili seeds. The experiment was conducted from March to June 2025 at the laboratory, field, and greenhouse facilities of the UPT for Rice and Palawija Seed Development, Singosari, Malang, East Java. A factorial completely randomized design (CRD) was employed with two factors: type of coating material (CMC, humic acid, and CMC + humic acid) and PGPR dosage (10 g and 20 g). The observed variables included maximum growth potential, germination rate, vigor index, and seedling growth rate. The results indicated that treatment with 1% humic acid + 20 g PGPR yielded the highest maximum growth potential and germination rate (100%), while the combination of 1% humic acid + 10 g PGPR produced the highest vigor index (33.33%) and growth rate (5.89%/day). The application of organic coating materials combined with PGPR was proven effective in restoring the physiological quality of aged chili seeds. These findings can be implemented as a seed invigoration strategy to extend the shelf life of horticultural seeds and improve seedling establishment under field conditions, thereby supporting sustainable crop production systems. Full text pdf